Development of a checklist framework for kidney transplantation - Nicolau-Raducu, Ramona; Ciancio, Gaetano; Raveh, Yehuda (Frontiers in Transplantation, 2024)
Background: Kidney transplantation is the therapy of choice for end-stage kidney disease, and a fast-growing transplant procedure worldwide. Diverse clinical practices for recipients and donors' selection and management between transplant centers hinder the creation and dissemination of an anesthesia-surgical checklist.Methods: Components of the anesthesia-surgical checklist were selected after a review of the English literature using PubMed search for donor, recipient and graft protocols and outcomes of existing practices in the field of kidney transplantation. Key elements of the most relevant articles were combined with our own center's experience and formulated into the proposed checklist. The checklist is intended to be used perioperatively, once patient receives an offer. Results: The perioperative checklist centers primarily on the following donor and recipient's factors: (i) Review of the pretransplant candidate workup; (ii) Assessment of donor/graft status; (iii) Hypothermic machine perfusion parameters; (iv) Operating room management; (v) Sign out. The proposed kidney transplant checklist was designed to ensure consistency and completeness of diverse tasks and facilitates team communication and coordination. Conclusion: We present a novel standardized combined anesthesia-surgical checklist framework for kidney transplant aimed at increasing perioperative safety and streamline the perioperative care of recipients. Future validation studies will determine its clinical feasibility and post-implementation efficacy.